Small sharp spikes as EEG markers of mesiotemporal lobe epilepsy. Issue 9 (September 2018) - Issa, Naoum P.; Wu, Shasha; Rose, Sandra; Towle, Vernon L.; Warnke, Peter C.; Tao, James X.
Highlights: Mesial temporal lobe epilepsy, a common type of focal epilepsy, often lacks scalp EEG correlates. Small sharp spikes on EEG were time-locked to hippocampal discharges recorded on intracranial electrodes. Small sharp spikes can be EEG markers of mesiotemporal lobe epilepsy rather than normal variants. Abstract: Objective: Mesial temporal lobe epilepsy (mTLE) is the most common type of focal epilepsy, but often lacks scalp EEG correlates. We ask if hippocampal epileptiform discharges that are characteristic of mTLE are associated with small sharp spikes (SSS) recorded on scalp EEG. SSS are considered benign waveforms, so are not currently used as markers of epilepsy. Methods: To determine if there is a relationship between SSS and hippocampal discharges, simultaneous scalp and hippocampal depth electrode EEGs were recorded from 27 patients being evaluated for possible mTLE. Scalp EEG waveforms were assessed at the time of hippocampal discharges identified on intracranial hippocampal depth electrodes. Results: 15 of 27 patients had SSS on scalp EEG that were time locked to hippocampal epileptiform discharges measured intracranially. These hippocampal spikes tended to have overlying high frequency oscillations and to co-localize with a seizure onset zone, suggesting that they were pathological discharges. Conclusions: There is a tight coupling between a subset of pathological hippocampal discharges and SSS. Significance: SSS can be scalp EEG markers of mTLE rather than normal EEG variants.